Partition functions related to identities of euler type - Mugwangwavari, Beaullah (My University, 2019)
In this research, we shall explore partition functions related to identities of Euler type, mainly focusing on identities due to P. A. MacMahon and M. V. Subbarao. We will give a new bijection for one of the partition theorems due to MacMahon and provide a generalisation of a partition identity due to Subbarao. We will further deduce parity formulas for various related partition functions. Our approach is via generating functions and bijective mappings.
A Dissertation Presented to the Faculty of Science, University of the Witwatersrand, Johannesburg in fulfilment of the requirements for the degree of Master of Science in Mathematics, October, 2019
Keywords: Partitions (Mathematics); Algebraic number theory; q-series